The Issue of Autonomy Within Multigrade Classrooms - Boix-Tomàs, Roser (2015)
When we speak of autonomy we think about how we navigate in a specific setting, since a relative level of autonomy is determined by that setting. When dealing with rural schools with multigrade classrooms, we refer to a setting comprising a complex diversity of people in terms of age, sex, grades, contexts, conceptual levels, interests, motivations... All of them sharing the same space and the same teacher, and organised within the same time span in which they share a set of activities, both spontaneous and/or planned by a teacher who must ensure learning achievement. This paper presents different types of autonomous learning in multigrade classrooms, as a result of an international competitive research carried out in several Latin American and European countries.